2019
DOI: 10.3390/d11070099
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Population Genetic Structure and Diversity between a Common (Chrysemys p. picta) and an Endangered (Clemmys guttata) Freshwater Turtle

Abstract: The northeastern United States has experienced dramatic alteration to its landscape since the time of European settlement. This alteration has had major impacts on the distribution and abundance of wildlife populations, but the legacy of this landscape change remains largely unexplored for most species of freshwater turtles. We used microsatellite markers to characterize and compare the population genetic structure and diversity between an abundant generalist, the eastern painted turtle (Chrysemys p. picta), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 80 publications
2
22
0
Order By: Relevance
“…Indeed, a positive value (maximum of 1) of internal relatedness (higher value of IR for the wild group than captive group) indicates that individuals are a result of consanguineous mating (O'Leary et al, 2013). Similarly, the higher value of HL (homozygosity by loci) for the wild population than the UMA indicates higher homozygosity in the wild group which could be result of higher inbreeding (Frankham et al, 2002 shown evidence of genetic isolation, genetic differentiation, as well as modest to high inbreeding rates, but surprisingly the values of heterozygosity in these species are medium to high (0.6-0.7) despite experiencing anthropogenic pressures (Buchanan et al, 2019;Gallego-Garc ıa et al, 2018;Mali et al, 2015a). As previously mentioned, the decrease in genetic diversity of many species of turtles, even after a prolonged decrease in population size, may not be observed due to their long generation times and late maturity associated with chelonian life history (Buchanan et al, 2019;Kuo & Janzen, 2004;Willoughby et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a positive value (maximum of 1) of internal relatedness (higher value of IR for the wild group than captive group) indicates that individuals are a result of consanguineous mating (O'Leary et al, 2013). Similarly, the higher value of HL (homozygosity by loci) for the wild population than the UMA indicates higher homozygosity in the wild group which could be result of higher inbreeding (Frankham et al, 2002 shown evidence of genetic isolation, genetic differentiation, as well as modest to high inbreeding rates, but surprisingly the values of heterozygosity in these species are medium to high (0.6-0.7) despite experiencing anthropogenic pressures (Buchanan et al, 2019;Gallego-Garc ıa et al, 2018;Mali et al, 2015a). As previously mentioned, the decrease in genetic diversity of many species of turtles, even after a prolonged decrease in population size, may not be observed due to their long generation times and late maturity associated with chelonian life history (Buchanan et al, 2019;Kuo & Janzen, 2004;Willoughby et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the higher value of HL (homozygosity by loci) for the wild population than the UMA indicates higher homozygosity in the wild group which could be result of higher inbreeding (Frankham et al., 2002). Several species of freshwater turtles, such as Apalone spinifera emoryi Agassiz, 1857 (Testudines, Trionychidae), Mesoclemmys dahli Zangerl & Medem, 1958 (Testudines, Chelidae), Chrysemys p. picta Schneider, 1783 (Testudines, Emydidae), and Clemmys guttata Schneider, 1792 (Testudines, Emydidae) have shown evidence of genetic isolation, genetic differentiation, as well as modest to high inbreeding rates, but surprisingly the values ​​of heterozygosity in these species are medium to high (0.6–0.7) despite experiencing anthropogenic pressures (Buchanan et al., 2019; Gallego-García et al., 2018; Mali et al., 2015a). As previously mentioned, the decrease in genetic diversity of many species of turtles, even after a prolonged decrease in population size, may not be observed due to their long generation times and late maturity associated with chelonian life history (Buchanan et al., 2019; Kuo & Janzen, 2004; Willoughby et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Within the natural environment, the dam itself becomes an artificial physical barrier that breaks the connectivity of the river (Bodie, 2001; Castello and Macedo, 2015; Chelazzi et al, 2007; Grill et al, 2019). One potential impact of dams is in modifying the habitats required among specialized species (Buchanan et al, 2019; Clark et al, 2018). It is common for freshwater turtles to be displaced or disappear when they cannot find the necessary conditions for their survival.…”
Section: Discussionmentioning
confidence: 99%
“…Although captive population (UMA) did not demonstrate a significant loss of heterozygotes, wild population shows significant loss of heterozygotes that could reveal high level of inbreeding and small population size that are probably a consequence of recent anthropogenic pressures (see above) on freshwater turtles in Tabasco state. Several species of freshwater turtles, such as Apalone spinifera emoryi Agassiz, 1857 (Testudines, Trionychidae), Mesoclemmys dahli Zangerl & Medem, 1958 (Testudines, Chelidae), Chrysemys p. picta Schneider, 1783 (Testudines, Emydidae), and Clemmys guttata Schneider, 1792 (Testudines, Emydidae) have shown evidence of genetic isolation, genetic differentiation as well as modest to high inbreeding rates, but surprisingly the values of heterozygosity in these species are medium to high (0.6-0.7) despite experiencing anthropogenic pressures [8284]. As mentioned before, the decrease in genetic diversity of many species of turtles, even after a prolonged decrease in population size, may not be observed due to their long generation times and late maturity associated with chelonian life history [8486].…”
Section: Discussionmentioning
confidence: 99%